Structural lesion in the brain is a risk factor of childhood intractable epilepsy - Islam, KA; Rahman, MM; Akhter, S; Alam, ST; Karim, KE (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):133-138 The abstract of this article is available on the PubMed website